2007
DOI: 10.3390/medicina43060062
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity of textile industry workers in Kaunas

Abstract: ĮvadasDarbo vietoje žmogus praleidžia didelę laiko dalį, todėl labai svarbu, kad darbo aplinkoje esantys rizikos veiksniai kuo mažiau neigiamai veiktų sveikatą. Kintančios darbo aplinkos sąlygos turi įtakos dirbančiųjų sveikatai, kurios pažeidimai yra specifiniai -tai priklauso nuo darbo pobūdžio, darbo stažo bei darbuotojų amžiaus (1).Lengvosios pramonės įmonėse dirbančiuosius veikia daug fizikinių bei cheminių rizikos veiksnių, kurie gali sukelti tiek profesines ligas, tiek turėti įtakos kitų ligų eigai. Tek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
7
1
Order By: Relevance
“…4,6,8,17,18 Present study showed respiratory tract infection 12.3% and acid peptic disease 7.3%, this was also in accordance with the study done in Rajasthan among textile workers males and females in 2005. 3 In this study on examination, 40% of the study subjects had refractive error, which is higher compared to other studies. This has to be addressed at the earliest as most (68%) of the workers were involved in fine work (stitching).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…4,6,8,17,18 Present study showed respiratory tract infection 12.3% and acid peptic disease 7.3%, this was also in accordance with the study done in Rajasthan among textile workers males and females in 2005. 3 In this study on examination, 40% of the study subjects had refractive error, which is higher compared to other studies. This has to be addressed at the earliest as most (68%) of the workers were involved in fine work (stitching).…”
Section: Discussioncontrasting
confidence: 55%
“…This not only affects their personal health and family but also the productivity of the company in the long run. 1,3 More than half of the study subjects had abnormal PEFR. This is high compared to the study done among textile workers in Karachi both genders in 2009.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Injuries were more frequent among men compared to women ([9.90 and 6.57 cases/100 workers/year], respectively [P < 0.05]). [14] Poland In a series of experiments performed in the Central Institute of Work Protection, Warsaw, Irena Franszczuk found that a noise band of median frequency of 4000 Hz and level 80-85 dB prolonged average simple reaction time in comparison with the average reaction time in silence. The simple reaction time measure was closely connected with the subjective feeling of annoyance.…”
Section: Fyr Macedoniamentioning
confidence: 99%
“…It was more concentrated on general health aspects with lack of attention to skin problems. According to the authors, the morbidity is not very high -1.94 sick leave cases in men and 2.29 in women per 100 workers a year (7). The Lithuanian Registry of Occupational Skin Diseases reports that throughout all occupational fields there were only 4 cases of occupational skin diseases in 2013 (8).…”
Section: Introductionmentioning
confidence: 99%